Tribocorrosion behavior of biofunctional titanium oxide films produced by micro-arc oxidation: Synergism and mechanisms. (July 2016) - Marques, Isabella da Silva Vieira; Alfaro, Maria Fernanda; Cruz, Nilson Cristino da; Mesquita, Marcelo Ferraz; Takoudis, Christos; Sukotjo, Cortino; Mathew, Mathew T.; Barão, Valentim Adelino Ricardo
Abstract: Dental implants, inserted into the oral cavity, are subjected to a synergistic interaction of wear and corrosion (tribocorrosion), which may lead to implant failures. The objective of this study was to investigate the tribocorrosion behavior of Ti oxide films produced by micro-arc oxidation (MAO) under oral environment simulation. MAO was conducted under different conditions as electrolyte composition: Ca/P (0.3 M/0.02 M or 0.1 M/0.03 M) incorporated with/without Ag (0.62 g/L) or Si (0.04 M); and treatment duration (5 and 10 min). Non-coated and sandblasted samples were used as controls. The surfaces morphology, topography and chemical composition were assessed to understand surface properties. ANOVA and Tukey׳s HSD tests were used ( α =0.05). Biofunctional porous oxide layers were obtained. Higher Ca/P produced larger porous and harder coatings when compared to non-coated group ( p <0.001), due to the presence of rutile crystalline structure. The total mass loss ( K wc ), which includes mass loss due to wear ( K w ) and that due to corrosion ( K c ) were determined. The dominant wear regime was found for higher Ca/P groups ( K c / K w ≈0.05) and a mechanism of wear-corrosion for controls and lower Ca/P groups ( K c / K w ≈0.11). The group treated for 10 min and enriched with Ag presented the lowest K wc ( p <0.05). Overall, MAO process was able to produce biofunctional oxide films with improved surface features, working as tribocorrosion resistant surfaces. Highlights: Biofunctional coatings were produced by micro-arc oxidation treatment. Surfaces with higher calcium concentration presented lower total mass loss values. Tribocorrosion resistant surfaces were produced due to the formation of rutile phase. Ag incorporation provided an increase in the resistance against wear and corrosion.